2002
DOI: 10.1099/00221287-148-8-2361
|View full text |Cite
|
Sign up to set email alerts
|

High-level resistance to class IIa bacteriocins is associated with one general mechanism in Listeria monocytogenes

Abstract: Class IIa bacteriocins may be used as natural food preservatives, yet resistance development in the target organisms is still poorly understood. In this study, the understanding of class IIa resistance development in Listeria monocytogenes is extended, linking the seemingly diverging results previously reported. Eight resistant mutants having a high resistance level (at least a 10 3 -fold increase in MIC), originating from five wild-type listerial strains, were independently isolated following exposure to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
160
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 27 publications
10
160
0
Order By: Relevance
“…This observation substantiates previous suggestions of a common mode of action for the class IIa bacteriocins against Ls. monocytogenes based on cross-resistance to these compounds (Ennahar et al, 2000a;Rasch & Knöchel, 1998) and also agrees with the general high-level resistance mechanism proposed for class IIa bacteriocins (Gravesen et al, 2002).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This observation substantiates previous suggestions of a common mode of action for the class IIa bacteriocins against Ls. monocytogenes based on cross-resistance to these compounds (Ennahar et al, 2000a;Rasch & Knöchel, 1998) and also agrees with the general high-level resistance mechanism proposed for class IIa bacteriocins (Gravesen et al, 2002).…”
Section: Discussionsupporting
confidence: 60%
“…lactis MG-ACD was insignificant at 156 ng leucocin ml 21 , which is similar to concentrations required for inhibition of Ls. monocytogenes (Gravesen et al, 2002;Vadyvaloo et al, 2002). Thus, the sensitivity to leucocin A increased at least 2500-fold when expression of mptACD was induced in Lc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The L. monocytogenes used in this study is a collection strain (ATCC) and the decrease of mptA gene expression has been reported only for resistant or mutant strains of L. monocytogenes [38,40,41]. Therefore the result of a non-significant increase in mptA gene expression in L. monocytogenes ATCC 7644 is consistent with the literature.…”
Section: Resultssupporting
confidence: 80%
“…The expression of this gene was highly suppressed after incubation for 240 h at 4 °C, and the treatment with nisin resulted in lower dltA expression as compared with the peptide P34. Previous studies have shown that a 1000-fold increased resistance to class IIa bacteriocins in L. monocytogenes and Enterococcus faecalis resulted from the loss of mptA expression [38,42,43]. The cell wall of L. monocytogenes is composed by a thick peptidoglycan layer containing two types of anionic polymers: teichoic acids (TA), which are covalently linked to the peptidoglycan, and lipoteichoic acids (LTAs), which are poly phosphoglycerols substituted with a Dalanyl ester or a glycosyl residue and anchored in the membrane by their glycolipid moiety [44].…”
Section: Resultsmentioning
confidence: 99%